Construction of a system for monitoring the state of technological equipment based on computer models - A. M. Ausiyevich; A. T. Skoybeda; S. S. Dounar; A. A. Kruglikau; E. M. Robilko; D. K. Rahman (Системный анализ и прикладная информатика, 2022)
The paper describes a method for condition monitoring of a complex mechanical system based on pre-computer FEM simulation of vibrations. The interrelation of vibrations of the connected elements of the system, described by transfer functions, is shown. The occurrence of resonant vibrations in directions orthogonal to the direction of the disturbing effect is revealed. The method for calculating of orthogonal direction vibration amplitudes can be based on measuring the values of the of vibrations in one direction and the regularities of the ratio of the amplitudes of vibrations.